Локомоция и характер обтекания тела при плавании гребенчатого тритона (Triturus cristatus Laur.) - Мордвинов, Ю.Е.; Хворов, С.А. (Вестник зоологии, 1980)
Experiments carried out in a water tank helped revealing the dependence for the swimming rate of Triturus cristatus Laurenti of various dimensions on the amplitude and frequency of the propulsor operation. The general index of the propulsor locomotor function distribution along the body longitudinal axis is calculated. The propulsor is of the eel-like type. A visualized picture of the counterflow around the animal body is obtained experimentally; the flow around the whole length of the body is determined to be continuous; conditions of macrovortic formation in the boundary layer and their separation at the point of the greatest body cross-section and further towards the tail are established.